Potent inhibition of human monoamine oxidase A and B by phenolic compounds and polyunsaturated fatty acids in tobacco smoke - Hong SW; Heydari A; Watson PR; Teesdale-Spittle PH; Page R; Northcote PT; Keyzers RA; Vyssotski M; Truman P (Elsevier B V, 2025)
Smoking is a main cause of premature death and preventable disease in the world. Interestingly, animal studies indicate that inhibition of monoamine oxidase (MAO), key enzymes for the degradation of neurotransmitters, increased self-administration of nicotine. The purpose of this study was to identify and characterize the potential MAO inhibitors in tobacco smoke responsible for MAO inhibition in smokers. A bioassay-guided isolation from an extract of tobacco smoke showed that catechol, 4-methylcatechol, hydroquinone, α-linolenic acid, and linoleic acid all displayed potent human MAO inhibitory activity. Additionally, the tobacco catechols 4-ethylcatechol and 4-vinylcatechol were included to test their inhibitory potencies. Catechol, 4-methylcatechol, 4-ethylcatechol, and hydroquinone are potent and irreversible MAO inhibitors. Among the phenolic compounds tested, 4-methylcatechol and 4-ethylcatechol inhibited MAO A with IC50 values of 10.0 and 12.6 μM, respectively, reducing to 0.27 and 0.43 μM after 1 h preincubation. In addition, α-linolenic acid and linoleic acid competitively inhibited MAO A with Ki values of 10.50 and 6.95 μM, respectively. These results suggest that MAO inhibition by phenolics and polyunsaturated fatty acids in tobacco smoke may be important contributors to the MAO inhibition experienced by smokers and to the enhancement of nicotine dependence this MAO inhibition is believed to cause.
Keywords: Monoamine oxidase inhibition; Tobacco; Catechols; Hydroquinone; PUFA; Addiction